THE EFFECT OF CAREER GUIDANCE ON CAREER PLANNING MATURITY IN STUDENTS AT MAS TAHFIDZ ROKAN HULU: STUDENTS WHO WILL CONTINUE THEIR EDUCATION IN SAUDI ARABIA: Pengaruh Bimbingan Karir terhadap Kematangan Perencanaan Karir Peserta Didik di MAS Tahfidz Rokan Hulu: Khususnya Peserta Didik yang akan Melanjutkan Studi ke Arab Saudi - Indri Reskiana Indri; Annisa Fadillah; Mhd Subhan (SOSIOEDUKASI, 2025)
This study aims to analyze the effect of career guidance on career planning maturity among students at MAS Tahfidz Rokan Hulu. The background of this research is based on the low ability of students to plan their future careers. Many students still lack mature career planning, are unable to explore career opportunities, and struggle with future decision-making. This study employed a quantitative correlational approach with a population consisting of all students at MAS Tahfidz Rokan Hulu and a sample of 34 students selected using purposive sampling. Data were collected using career guidance and career planning maturity questionnaires and analyzed using Pearson’s Product Moment correlation. The results showed a positive and significant influence of career guidance on students’ career planning maturity at MAS Tahfidz Rokan Hulu. Students who actively participated in career guidance services demonstrated better self-understanding, recognized their potential, made more mature decisions, and developed clearer and more directed future career plans. This study emphasizes the importance of systematic career guidance conducted by guidance and counseling teachers to help students prepare for their future careers, choose educational paths aligned with their talents and interests, and achieve their future goals—especially for those planning to continue their studies in Saudi Arabia.